The science of stress management a guide to best practices for better well-being - Dasgupta, Amitava 1958- (Rowman & Littlefield, 2018)
"Stress is an inevitable part of everyday life. Sometimes we manage it well. Other times, not so much. But understanding the role of stress in our overall health and wellness is essential to taking it head-on. It's not just that stress can take over our thoughts; it can take over our bodies. From the flight or fight response to inflammation, from feeling anxious to feeling sick, it can deteriorate our bodies and our minds from the inside out. While many books promise tips on managing stress, this book takes it one step further to consider the science behind stress and how it affects our minds and bodies, offering evidence-based approaches to managing stress for optimum results. Amitava Dasgupta guides readers to a greater understanding of the mechanisms at work when stress is present and provides guidance for dealing with those physical and mental responses. While grounded in the science of stress, this work also helps readers employ those strategies that will best manage stress for better overall health."--Book jacket.